THE DEFINITION OF THE ROLE AND DIRECTIONS OF DEVELOPMENT OF FRANCHISING IN RUSSIA - E. B. Atueva (Вестник Дагестанского государственного технического университета: Технические науки)
The franchise is currently one of the most effective tools to enhance the efficiency of small business. It gives an opportunity to combine the advantages of small and large business. Theenterprises receiving advanced technology and support on the basis of franchising, become more competitive. The system of franchising every year becomes more and more popular with Russian entrepreneurs. While on the path of its effective development raises a number of issues requiring systematic solutions.